Taguchi‐based robust design for minimising torque ripple in 6‐slot/2‐pole modular high‐speed permanent magnet motor with manufacturing tolerances - Dong Xiang; Zi‐Qiang Zhu; Dawei Liang; Fan Xu; Tianran He (IET Electric Power Applications)
Abstract A Taguchi‐based robust design strategy is proposed to minimise the torque ripple of a 6‐slot/2‐pole modular high‐speed permanent magnet motor in mass production, accounting for manufacturing tolerances of split gap (Δg), misalignment (Δm), and offset angle (Δα). Firstly, the effects and interactions of manufacturing tolerances are calculated, indicating that Δg has the highest effect followed by Δm, positive Δg and negative Δm have a strengthening effect, and Δα has no effect, and subsequently, the worst‐case scenario of manufacturing tolerances with the highest torque ripple is obtained. Afterwards, tooth circumferential positions are optimised for minimising torque ripple without jeopardising average torque, considering the tradeoff between the cases without manufacturing tolerance and with the worst‐case scenario of manufacturing tolerances. As will be demonstrated, torque ripples are reduced significantly, that is, they are particularly reduced by 40% in the worst‐case scenario. Under hypothetical 100 sets manufacturing tolerances as Gauss distributions, the optimised machines have significantly reduced torque ripples (maximum and average reductions are 33% and 16%, respectively) with more concentrated distribution. The correctness of the methods is verified by experimental validation.